RELASI PROFESI GURU DAN ORGANISASI GURU SEBAGAI HAK WARGA NEGARA - Pristiwiyanto Pristiwiyanto (Pedir Research Institut, 2021)
Profession is a job or position that requires certain skills, but requires preparation through special education and training. In essence, the profession is a statement or an open promise stating that a person is devoting himself to a position. The teacher profession is a professional educator with the main task of educating, teach, guide, direct, train and assess. Teachers are classified as professions because according to their expertise and special requirements in carrying out their duties, they have a professional organization with a code of ethics, and have an organizational platform. The teacher professional organization is a rational coordination of the activities of a number of teachers to achieve shared educational goals that are explicitly formulated, through regulation (code of ethics) and division of labor as well as through a hierarchy of power and professional responsibilities. This study aims to describe the relationship between the teaching profession and teacher organizations. The research method used is quantitative methods. The data collection techniques used in this study used questionnaires, tests and interviews. The results of this study indicate that there is a relationship between the teaching profession and teacher organizations.